(untitled) (Acta Polytechnica CTU Proceedings, 2016)
This paper focuses on selected problem areas in the implementation of ETCS L3, analyz-es their impacts and offers a number of possible solutions as a basis for pilot testing. It compares the suitability of each solution and summarizes their advantages and disadvantages.